TINEA KORPORIS - Saraswati, Yara Egyptha; Darmada, IGK; Mas Rusyati, Luh Made (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Tinea corporis is a superficial dermatophyte infection characterized by either inflammatory or non inflammatory lesion on the glabrous skin. Trichophyton rubrum is a common dermatophyte for tinea corporis. Tinea corporis occurs in both men and women, affects persons of all age group, but prevalence is highest in predolescents. Tinea corporis infections may present as an annular erythematous plaque with raised leading edge and scaling. Tinea corporis can also present in non-ringworm fashion, where it may manifest as an erythematous papule or a series of vesicles.Topical therapy is recommended for a localized infection and systemic therapy maybe indicated for tinea corporis that includes extensive skin infection immunosupression. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Tinea Corporis, Dermatophyte, Ringworm